Effect of Different Plant Extracts Added to Ice on Sensory Preference of Sliced Salmon - Hande Doğruyol; Şafak Ulusoy; Sühendan Mol; Didem Üçok (Aquatic Sciences and Engineering)
almon is usually sold in slices on ice in retail markets. Since ice is in direct contact with fish, it affects the sensory characteristics as well as the physicochemical properties. Improving the properties of ice can make positive contributions to fish flavor and consumer preference. In this study, sliced salmons were treated with ice containing one of either basil (B), rosemary (R), laurel (L), oregano (O) or fennel (F) extracts. Iced salmon without any plant extract was the control (C) group. Displaying sliced fish for sale on ice and placing back to cold room at the end of the day is a common practice. Samples were covered with ice, stored at 18±1°C during daytime and taken to the cold room (2±1°C) at night to simulate marketing conditions. Adding plant extracts to ice resulted in a remarkable change in fish flavor, and R, F, and L were the most popular treatments among all groups. In particular, rosemary-added ice significantly (P<0.05) increased the preference of consumption. Panelists emphasized that F samples can be consumed as appetizers. Dominant and pleasant aroma was also stated for L samples. The mesophilic aerobic bacteria count remained below 5 log CFU/g in all samples during 4 days. The total volatile basic nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS) and pH values of all groups remained within the limits of acceptability. Using plant extract-added-ice provided a suitable quality sale of salmon for 4 days and offered an option to consumers by giving the product different flavors.